비파(Eriobotrya japonica) 열매 추출물의 산화방지능과 미백 효과 - 윤민규(Min-Kyu Yun); 박기철(Gi-Cheol Park); 조윤섭(Youn-Sup Cho); 김대옥(Dae-Ok Kim) (한국식품과학회지, 2022)
The loquat (Eriobotrya japonica) is a fruit tree belonging to the Rosaceae family. Loquat fruit extracts from three cultivars (Tanaka, Mogi, and Jinwang) were prepared using absolute methanol and homogenization and ultrasound sonication procedures. We measured the total phenolic and flavonoid content of the fruit extracts and their antioxidant capacities. In addition, we evaluated tyrosinase activity and anti-melanogenic effects in B16F1 melanoma cells. The fruit extract from cv. Tanaka had the highest total phenolic content and showed the highest antioxidant capacity in the ABTS assay. The loquat fruit extract from cv. Jinwang had the highest total flavonoid content and showed the highest antioxidant capacity in the DPPH assay. Loquat fruit extracts from the Tanaka and Jinwang cultivars effectively inhibited mushroom tyrosinase activity. The loquat fruit extracts reduced intracellular oxidative stress in B16F1 melanoma cells. Treating B16F1 melanoma cells with loquat fruit extract from cv. Tanaka at a concentration of 125 ㎍/mL effectively inhibited melanin synthesis. However, treating the B16F1 melanoma cells with loquat fruit extracts from the Jinwang and Mogi cultivars did not. These results suggest that loquat fruit extracts from the Tanaka cultivar may serve as potential sources of antioxidants and act as a skin-whitening agent. 비파 열매 추출물의 총페놀 함량, 총플라보노드 함량, 산화방지능을 확인한 결과 전중 열매에서 가장 높은 총페놀 함량과 산화방지능(ABTS법)을 보였다. 진왕 열매는 전중 열매와 비교하여 총페놀 함량은 유의적으로 낮았지만, 가장 높은 총플라보노이드 함량과 산화방지능(DPPH법)을 보여주었다. 세 품종의 비파 열매추출물은 B16F1 흑색종 세포 내 산화스트레스를 감소시켰으며, 특히 전중과 진왕 열매 추출물은 멜라닌 합성에 관여하는 타이로시네이즈 활성을 효과적으로 감소시켰다. 하지만 전중 열매 추출물(125 ㎍/mL)을 제외한 모든 처리군에서 멜라닌 생성을 효과적으로 저해시키지는 못하였다. 본 연구 결과를 바탕으로 전중품종의 열매 추출물은 천연 산화방지제 및 피부미백 소재로의 활용 가치가 있는 것으로 판단된다.